2011
DOI: 10.1055/s-0031-1280346
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV and Cycloastragenol Stimulate the Phosphorylation of Extracellular Signal-Regulated Protein Kinase in Multiple Cell Types

Abstract: Two Chinese herb-derived small molecule telomerase activators, astragaloside IV (AG-IV) and cycloastragenol (CAG), have recently been shown to improve the proliferative response of CD8+ T lymphocytes from HIV-infected patients by upregulating telomerase activity. Here, we examined the signaling mechanism of AG-IV and CAG. Telomerase activity in human embryonic kidney HEK293 fibroblasts was increased upon treatment with increasing concentrations of AG-IV or CAG. Both compounds induced the phosphorylation of ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…AS-IV, as one of its active elements, has been revealed its pharmacological mechanisms to some degree. Recent researches have suggested that AS-IV might protect from cardiomyopathy via diverse effects upon a variety of intracellular signaling pathways, including the activation of Src/mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase (ERK) pathway, 22) inhibiting tumor growth factor (TGF)-β1 23) and ERK1/2 signaling pathways, 24) upregulating superoxide dismutase-1 levels, 3,25) antioxidative and nitric oxide-inducing pathway, 26) and improving intracellular calcium handling. 27,28) The aim of our study is to clarify the basic electrophysiological effects of AS-IV on cardiac myocytes, and we have found that AS-IV prolonged APd, and decreased I K and I CaL in guinea-pig cardiac myocytes.…”
Section: Effects Of As-iv On Na + Currentsmentioning
confidence: 99%
“…AS-IV, as one of its active elements, has been revealed its pharmacological mechanisms to some degree. Recent researches have suggested that AS-IV might protect from cardiomyopathy via diverse effects upon a variety of intracellular signaling pathways, including the activation of Src/mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase (ERK) pathway, 22) inhibiting tumor growth factor (TGF)-β1 23) and ERK1/2 signaling pathways, 24) upregulating superoxide dismutase-1 levels, 3,25) antioxidative and nitric oxide-inducing pathway, 26) and improving intracellular calcium handling. 27,28) The aim of our study is to clarify the basic electrophysiological effects of AS-IV on cardiac myocytes, and we have found that AS-IV prolonged APd, and decreased I K and I CaL in guinea-pig cardiac myocytes.…”
Section: Effects Of As-iv On Na + Currentsmentioning
confidence: 99%
“…293 cell line: of kidney or adrenal gland origin and epithelial or neuronal phenotype? 293 cells have been considered the kidney embryonic epithelial cells (e.g., Ashokkumar et al, 2006;Cusick et al, 2010) or even fibroblasts (e.g., Cooper et al, 1998;Yung et al, 2012) and shown to express markers of a kidney developmental stage between the condensed mesenchyme and epithelial S-shaped body but not markers of the differentiated tubular segments, proximal tubules or collecting ducts (Torban and Goodyer, 1998). Moreover, an ectopic expression of transcription factor paired box gene 2 (PAX2), relevant to an early stage of nephrogenesis, modified vimentin, E-cadherin and Wilms tumor 1 expression in 293 cells in such a manner as it occurs during the mesenchymeepithelium transition of early nephrogenesis in vivo (Torban and Goodyer, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This aglycone of astragaloside IV effectively enhances the antiviral response in human CD8+ T-lymphocytes through its distinct telomerase-promoting activity [28]. Furthermore, we demonstrated that CAG stimulates the phosphorylation of extracellular signal-regulated proteins in multiple cell lines and is absorbed via the intestinal epithelium [29,30]. Importantly, we have evaluated the pharmacological effects of CAG in neuronal cells as well as its effects on depression-like behaviors in mice.…”
Section: Introductionmentioning
confidence: 99%